Il teatro: i concetti e la cosa: Una viva discussione tra Alain Badiou e Bruno Tackels - Badiou, Alain; Tackels, Bruno; Attisani, Antonio (Mimesis Journal, 2016)
The philosopher Alain Badiou, also a playwright and former collaborator of Antoine Vitez, has been active for many years in the arena of vivacious discussions that, at least in France, concern the future of the theater. Since many years his stances, often polemical, aroused opinions with the opposite sign. While in Italy they are proceeding to the publication of various writings by and about the philosopher, our journal has chosen to present the philosopher theatrical thinking along with excerpts of the interventions of Bruno Tackels, another in uential philosopher and theatrical operator, that are a straightforward opposition to Badiou’s arguments.